FROM INDUSTRIAL WASTES TO RECOVERED AND REUSED MATERIALS IN BUILDING INDUSTRY - Luminita Georgeta POPESCU; Sabin Cristian DIMULESCU (Fiabilitate şi Durabilitate)
In this paper we will continue to present the results obtained through the research carried out in order to identify new solution for the recovery of waste from industry. The paper presents concrete domains of use of industrial waste from either the energy industry or the construction industry.